Applications of multispectral autofluorescence imaging of malignant tumors - G. V. Papayan; N. N. Petrishchev; S. V. Kim; Hyung Ho Kim; V. B. Berezin; Uk Kang (Biomedical Photonics)
The applications of multispectral autofluorescence imaging of malignant tumor was shown in in vitro and in vivo experiments. Using ТС-1 mouse tumor model it was demonstrated that the location of tumor formation can be clearly identified as early as 2 days after injection of tumor cells. Among observed effects the new one is an unusually active angiogenesis at early stage of tumor formation accompanied by atypical tortuous vessels with growth rate up to 3 mm/day. Two-wave excitation simultaneous laser with excitation on wavelength of 390 nm and 635 nm is shown to be promising for autofluorescence diagnosis along with single-wave excitation which is conventionally performed in the violet-blue region of the spectrum. This mode of excitation allows detecting the increased level of protoporphyrin IX even at early stage of carcinogenesis. The fluorescence due to active synthesis of protoporphyrin IX was shown to correlate with density of vessels. Increase of this fluorescence is observed also for aseptic inflammation but it has diffuse pattern which allows differentiating it from local fluorescence image at the site of tumor formation. The possibility of successful achievement of high-quality image using multispectral imaging and also optimization of registration settings were demonstrated in the experiment. The study of surgical specimen showed capabilities of imaging and measurement of autofluorescence in tumor tissue. The obtained results are intended to help in the development of endoscopic methods of imaging and devices for diagnosis of early tumors.